2013
DOI: 10.1177/1534508413513315
|View full text |Cite
|
Sign up to set email alerts
|

Special Education Teacher Evaluation

Abstract: There is currently little consensus on how special education teachers should be evaluated. The lack of consensus may be due to several reasons. Special education teachers work under a variety of complex conditions, with a very heterogeneous population, and support student progress toward a very individualized set of goals. In addition, special education is marked by historical rates of attrition, with a lack of highly qualified teachers entering the field, and a number of special education teachers completing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…Although the time to skill completion was fastest with VM+P&R for Jake and Pete, both students required fewer minutes of instructional time with P&R than either of the videobased interventions. This is due in large part to the amount of time required to sit and view the video, but is an important consideration given that teachers are constantly struggling to find sufficient time to plan and deliver instruction (Johnson & Semmelroth, 2014). Compounding this argument is the fact that it took 40 minutes to create one video while no prep time was needed to implement P&R.…”
Section: Vm+pandr Respondersmentioning
confidence: 99%
“…Although the time to skill completion was fastest with VM+P&R for Jake and Pete, both students required fewer minutes of instructional time with P&R than either of the videobased interventions. This is due in large part to the amount of time required to sit and view the video, but is an important consideration given that teachers are constantly struggling to find sufficient time to plan and deliver instruction (Johnson & Semmelroth, 2014). Compounding this argument is the fact that it took 40 minutes to create one video while no prep time was needed to implement P&R.…”
Section: Vm+pandr Respondersmentioning
confidence: 99%
“…A growing body of conceptual literature has examined whether teacher evaluation measures originally designed for general educators are appropriate for special educators (Johnson & Semmelroth, 2014;Jones & Brownell, 2014;Jones et al, 2013). At the same time, there has been less empirical research on special educators' perceptions of or experiences with new approaches to teacher evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, special educators tend to focus their work on individual students with disabilities (SWDs) as opposed to whole classes of students and are typically responsible for such tasks as creating and enacting Individualized Education Programs (IEPs), adapting curriculum and assessments, and overseeing student progress (Jones, 2016). Additionally, special educators frequently provide explicit, teacher-directed instruction to individual students (Johnson & Semmelroth, 2014;Jones & Brownell, 2014). It is important to be mindful of such differences in work responsibilities between special and general educators when evaluating research on how each type of teacher is evaluated.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to increase implementation of research-based practices may be the use of teacher observation instruments designed for intervention settings (i.e., settings in which SMD are receiving additional instruction to remediate specific areas of difficulty or support development of proficiency). Such instruments should provide reliable and accurate feedback to teachers that is aligned with content-specific practices found to improve achievement for SMD (Johnson & Semmelroth, 2014). Although there are observation instruments that focus on mathematics instruction in general education settings (e.g., MQI, Learning Mathematics for Teaching Project, 2011;RTOP, Sawada et al, 2002), these instruments are not fully aligned with practices identified as most effective for SMD in interventions.…”
Section: Introductionmentioning
confidence: 99%